Mengkonfirmasi Ulang Kemesiasan Judaisme di Era Antar Testament (Sebuah Pengenalan ke dalam Perjanjian Lama) - Yosef, Hery Budi (Pusat Studi Pentakosta Indonesia, 2022)
This article presents some of the messianic thoughts that fall within the range of the Inter-Testament especially on the apocryphal books. The author begins with some important terms about the